The Role and Strategy of Schools in Financing Education to Improve Education Quality - Aziziyah, Atiyah; Ahmad, Masduki (Journal of Educational Sciences, 2024)
Many of the problems that occur in the implementation of education in Indonesia are not only due to the education system but can also be suspected to be due to the perpetrators of the education providers themselves. In reality, there are still quite a lot of school-age people who do not go to school because of the problem of expensive education costs. Thus, in conditions of very limited funds and schools faced with diverse needs, schools must be able to make decisions while still being guided by quality improvement. This study aims to analyze the role and strategy of schools in financing education to improve the quality of education. The research method used is a qualitative method with a descriptive approach. Data collection was conducted through preliminary analysis of teachers and principals, observations to schools, and interviews of administration staff, teachers and principals at SMA PGRI 12 Jakarta. The results showed that one of the factors that influence the quality of education in a school is the role and strategy of the school in managing its education financing. Thus, the correlation created between school financing and the quality of education can be clearly seen in teaching and learning activities.